The Experiences of Multiple Sclerosis Patients’ Family Caregivers at the First Hospitalization of Their Patients: A Qualitative Study - Tehranineshat, Banafsheh (Patient Prefer Adherence, 2020)
BACKGROUND AND AIM: Being diagnosed with multiple sclerosis is usually accompanied by emotional trauma for patients and their families. The chronic, progressive, and unpredictable nature of the disease spells the patients’ long-term need for care from their families. As soon as a diagnosis is made, family caregivers are faced with many challenges. The present study aims to identify family caregivers’ experiences at the first hospitalization of their patients. MATERIALS AND METHODS: The present study is a work of qualitative research and uses the conventional content analysis approach. It lasted from July 2019 to March 2020. The subjects were selected via purposeful sampling. To collect data, the researchers conducted in-depth, semi-structured interviews with 18 family caregivers of patients with multiple sclerosis. The collected data were analyzed using MAXQDA 2007. RESULTS: Analysis of the data yielded three themes: peaceful environment, need for continuing full support, and religion-based coping strategies. CONCLUSION: The findings of the present study can be used to develop support programs that address family caregivers’ problems and needs to assist them in accepting and coping with the conditions of their patients, thereby increasing the quality of care provided to patients with multiple sclerosis.